Análisis de tiempo para la mejora de procesos de horas de vinculación y actualización docente de la ESPAM MFL - Alcívar Murillo, Dayana Sofía (2018)
This research was aimed to the timing analysis of the teacher’s linking and update hours at ESPAM MFL, in order to establish a proposal for the improvement to the determined sub processes accomplishing what it was stated, interviews were given to the managers of the linking department in each career and the post-graduate director, who provided information on how the processes and sub processes are carried out under each of their jurisdictions, the methods were also applied, which helped to obtain a clear analysis and realize a procedure standardization that improve the times of linking hours and the teacher’s update to meet the objectives set out in this research, with this it was possible to describe the management processes on the linking and update hours carried out at ESPAM MFL, starting from the application of the interview technique (to those responsible of the linking department in each career and the postgraduate director) after the application of direct observation in order to measure the amount of work, another of the objectives was to graphically demonstrate the management processes of the teachers’ linking and updating hours by using the AS-IS technique, to the analysis and interpretation of the data obtained and the elaboration of an improvement plan to be able to optimize the aforementioned processes and sub processes, and it was concluded that a regulation should be created to establish the activities to be carried out in order to execute each procedure.